Crisis Communication Strategies of East Java Regional Police Public Relations in Building a Positive Image Through TikTok - Andi Afdu Burhanuddin (Nusantara Society Lab, 2025)
The Indonesian National Police often face crises of public trust and negative public image, which are caused by the spread of negative issues on social media. In this scientific article, the researcher analyze the crisis communication strategies implemented by the Public Relations Division of the East Java Regional Police (Humas Polda Jatim) in response to the growing negative issues about the police circulating among the public. This research aims to understand how Humas Polda Jatim applies crisis communication strategies on the TikTok social media platform to address negative issues regarding the police and build a positive image, as well as how these strategies are used to create two-way communication between the police and the public through content posted on the official TikTok account of Humas Polda Jatim. Therefore, the researcher employs a qualitative approach to compile data obtained from interviews with relevant informants in order to provide clear explanations and insights. The research presented in this scientific article is expected to serve as a reference for relevant articles that may be developed in the future.